(untitled) - Levenspiel, Octave (New York, 2006)
The purpose of this book is to teach how to answer these questions reliably and wisely. To do this the author emphasizes qualitative arguments, simple design methods, graphical procedures, and frequent comparision of the major reaction types. This approach should help develop a strong intuitive sence for good design which can then guide and reinforce the formal methods.
Kỹ thuật phản ứng dị thể
Keywords: Chemical reactors,Những phản ứng hóa học